2022
DOI: 10.1101/2022.10.27.513845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translesion DNA synthesis polymerase κ is essential to a carcinogen-induced nucleolar stress response

Abstract: DNA polymerase kappa (Polk) has multiple cellular roles such as translesion DNA synthesis, replication of repetitive sequences and nucleotide excision repair. Since multiple polymerases are present at the same DNA lesion, by utilizing the selective Polk substrate, N2 (4 ethynylbenyl) 2 deoxyguanosine (EBndG) as bait, isolation of proteins on Pol kappa synthesized DNA (iPoKD) followed by mass spectrometry captured proteins associated specifically with nascent DNA synthesized with Polk. We show that, Polk is act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 112 publications
(203 reference statements)
1
4
0
Order By: Relevance
“…To confirm the biochemical result, we used an immunofluorescence (IF) assay to visualize the spatial-temporal changes of POLK with age in a healthy wild-type mouse brain. We validated the POLK antibody, previously reported in immunofluorescence assays in human cell lines (Paul et al 2022), using mouse primary neuronal culture and observed a significant decrease in POLK signal upon two independent siRNA knock-downs but not in scrambled siRNA (Figure S1Ci). qPCR analysis showed a 35% reduction in Polk mRNA level upon siRNA knock-down (Figure S1Cii).…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…To confirm the biochemical result, we used an immunofluorescence (IF) assay to visualize the spatial-temporal changes of POLK with age in a healthy wild-type mouse brain. We validated the POLK antibody, previously reported in immunofluorescence assays in human cell lines (Paul et al 2022), using mouse primary neuronal culture and observed a significant decrease in POLK signal upon two independent siRNA knock-downs but not in scrambled siRNA (Figure S1Ci). qPCR analysis showed a 35% reduction in Polk mRNA level upon siRNA knock-down (Figure S1Cii).…”
Section: Resultssupporting
confidence: 53%
“…A progressive age-associated shiJ in subcellular localiza;on of Polk First, we validated the an4-POLK an4body for immunofluorescence assays by knocking out Polk in the U2OS cell line 33 and recovering endogenous POLK by immunoprecipita4on from cor4cal 4ssue. Compara4ve semiquan4ta4ve western blot of nuclear frac4ons from cor4cal 4ssue showed that POLK levels decreased with increasing age 1 month, versus 10 months and 18 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations